Perceptions of exercise for older people living with dementia in Bangkok, Thailand: an exploratory qualitative study. (14th July 2015) - Karuncharernpanit, Sirikul; Hendricks, Joyce; Toye, Christine
Abstract : Background: Dementia is a significant issue globally, including in Thailand, and exercise is known to have health benefits for people living with dementia. However, little is known about exercise acceptable to, and feasible for, this population group in low‐to‐middle income countries although, more broadly, it is recognised that health‐related behaviours are influenced by the perceptions of the individual, which exist within a cultural context. Objectives: To explore and describe perceptions of appropriate exercise for people living with dementia in Bangkok, Thailand. Design: Qualitative exploratory descriptive. Setting: Bangkok, Thailand. Participants: Nine professionals – experts in exercise, dementia care and relevant policy development – and nine dyads of people with dementia and their family caregivers all recruited using purposive sampling. Methods: Semi‐structured interviews subjected to thematic analysis. Results: Three themes emerged: how exercise was defined, perceived benefits of exercise and how exercise should be implemented. Professionals recognised three exercise elements: aerobic exercise plus balance and strength training. Dyads recognised home‐based activities (e.g., housework) and walking. Both groups recognised benefits of exercise in maintaining health and function and improving mood and sleep. Only health professionals identified falls risk reduction. There was limited appreciation of benefits for caregivers by maintaining function in care recipients. Professionals deemed that exercise should address all three elements, using easily accessible low‐cost resources. The need for safety was emphasised, and there was agreement that in‐home exercise was appropriate. Family/cultural values were evident that could present barriers to exercise implementation. Conclusion: Changing health‐related behaviours requires an understanding of individual perspectives, which exist within a cultural context. This study has illuminated the Thai context and has implications beyond this. Findings emphasise a need for potential benefits to be sufficiently understood by family caregivers to overcome any culturally based reluctance to promote exercise in older people. Implications for practice: Nurses have a key role in supporting care givers of older persons with dementia supervise home based exercise. Nurses need to develop knowledge of aerobic exercise to teach caregivers and the older person with dementia. Muscle strength and aerobic exercise assists in the older person's ability to undertake ADL.